Liver enzymes and clustering cardiometabolic risk factors in European adolescents: the HELENA study. Issue 5 (17th December 2014) - Labayen, I.; Ruiz, J. R.; Ortega, F. B.; Davis, C. L.; Rodríguez, G.; González‐Gross, M.; Breidenassel, C.; Dallongeville, J.; Marcos, A.; Widhalm, K.; Kafatos, A.; Molnar, D.; et al.
Summary: Objectives: This study aimed to explore the associations of liver biomarkers with cardiometabolic risk factors and their clustering, and to provide reference values (percentiles) and cut‐off points for liver biomarkers associated with high cardiometabolic risk in European adolescents. Methods: Alanine aminotransferase (ALT), gamma‐glutamyltransferase (GGT), aspartate aminotransferase to ALT ratio (AST/ALT), waist circumference, blood pressure, triglycerides, high‐density lipoprotein cholesterol and insulin were measured in 1084 adolescents. We computed a continuous cardiometabolic risk score and defined the high cardiometabolic risk. Results: Higher ALT and GGT and lower AST/ALT were associated with adiposity and with the number of adverse cardiometabolic risk factors ( P s < 0.05). Higher GGT and lower AST/ALT were associated with higher cardiometabolic risk score ( P s < 0.001) in males and females, and ALT only in males ( P s < 0.001). Gender‐ and age‐specific percentiles for liver biomarkers were provided. Receiver operating characteristic analyses showed a significant discriminatory accuracy of AST/ALT in identifying the low/high cardiometabolic risk ( P s < 0.01) and thresholds were provided. Conclusions: Higher GGT and lower AST/ALT are associated with higher cardiometabolic risk factors and their clustering in male and female European adolescents, whereas the associations of ALT were gender dependent. Our results suggest the usefulness of AST/ALT as a screening test in the assessment of adolescents with high cardiometabolic risk and provide gender‐ and age‐specific thresholds that might be of clinical interest.